Demographic and sexual risk predictors of delay discounting of condom-protected sex. Issue 3 (3rd March 2020) - Sweeney, Mary M.; Berry, Meredith S.; Johnson, Patrick S.; Herrmann, Evan S.; Meredith, Steven E.; Johnson, Matthew W.
Abstract: Objective: Sexual delay discounting describes the decreased likelihood of condom-protected sex if a condom is not immediately available, which can be quantitatively summarised using the Sexual Delay Discounting Task (SDDT). The present studies determined the extent to which condom use likelihood as assessed by the SDDT is associated with self-reported sexual risk behaviours and demographics in two online samples of adults. Design: Study 1 ( n = 767) assessed demographics, sexual risk behaviour, and delay discounting, and examined relations between these variables using correlation and regression. Study 2 ( n = 267) examined whether real-world instances of unprotected sex because a condom was not immediately available predicted greater sexual discounting. Main outcome measures: Sexual delay discounting, condom use. Results: Both studies observed significant positive relations between sexual delay discounting and self-reported sexual risk behaviours, and found that males tended to show greater sexual discounting. In Study 2, 46% of the sample self-reported having unprotected sex because a condom was not immediately available, and these individuals showed significantly greater sexual delay discounting. Conclusion: These results extend prior findings by demonstrating that delay is a critical variable underlying real-life sexual risk behaviour among non-clinical samples. The SDDT is an ecologically valid measure of these processes.